Bridgeless Cuk Converter with Fuzzy Controller for Power Quality Enhancement of PV Integrated EV Charger - et. al., G. Niteesh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a new output is explored by Bridge Less (BL) Cuk Converter using fuzzy logic controller algorithm for integrated PV electrical vehicle charger (battery). The minimum switch numbers are used to charge the battery at optimum cost in this proposed technique. Stationary voltages and current inputs are achieved despite the unbalanced load operation of the EV-charger i.e. under load, nominal load or overload operation. Also under imbalance of the input supply it retains constant battery parameters. The BL-Cuk converter with fuzzy controller is used to achieve robustness. The proposed technology uses a reduced amount of switching, so the loss of drive is minimal and no DC condenser is required. Therefore, over traditional EV charging approaches, balance voltage is generated across the condenser.